Pengaruh Kualitas Tidur dan Aktivitas Fisik pada Pasien Hipertensi di Puskesmas Ngajum, Kabupaten Malang - Fitria Nugraha Aini; Dewi Martha Indria; Rizky Setia Firdaus; Ardhita Okky Riyana Dewi; Roziq Siroj Ramadhan; Cornellia Agnes Fransiska Putri (Jurnal Kesehatan Islam : Islamic Health Journal, 2022)
Sleep quality affects overall health and quality of life, including blood pressure. Increased blood pressure or hypertension is one of the factors causing cardiovascular disease that is often found in primary health care. Based on Riskesdas data in 2018, 25.8% of the Indonesian population suffers from hypertension. This study aims to determine the effect of sleep quality and level of physical activity with the incidence of hypertension in patients at the Ngajum Public Health Center, Malang Regency. Method: The research design used is a case control study. This research was conducted on 60 respondents in the working area of the Ngajum Health Center, Ngajum District, Malang Regency in December 2019. Sampling was carried out using the purposive sampling method. The research instrument used a sleep quality questionnaire adopted from the Pittsburgh Sleep Quality Index (PSQI) and a physical activity questionnaire adopted from the Global Physical Activity Questionnaire (GPAQ). Results: The case group consisted of 30 hypertensive patients and the control group consisted of 30 non-hypertensive patients. In the hypertension group, 23.3% of patients had good sleep quality and 76.7% had poor sleep quality. In the group of non-hypertensive patients, 73.3% had good sleep quality and 26.7% had poor sleep quality (p≤0.05). Meanwhile, the level of physical activity in hypertensive patients was 60.0% who had high activity, 6.7% had moderate activity, and 33.3% had low activity. Then in the control group there were 70.0% who had high activity, 20.0% had moderate activity, and 10.0% had low activity (p≤0,05). Conclusion: Based on the results of the study, it can be concluded that the quality of sleep and activity had a significant effect on the incidence of hypertension in patients at the Ngajum Public Health Center, Ngajum District, Malang Regency.